Addressing the Cultivation of Teachers’ Reflection Skills via Virtual Reality Based Methodology - Stavroulia, Kalliopi Evangelia; Lanitis, Andreas (My University, 2019)
Virtual Reality (VR) based approaches have emerged lately as a new learning and training paradigm. This paper addresses the possibility to cultivate teacher’s reflection skills using a VR based approach targeting to maximize their professional development. Reflection has been considered as a skill of paramount importance for teachers and an integral part of their professional development. The research aimed to investigate possible difference in cultivating reflection skills between participants who used a VR system and the control group who participated in a real classroom setting. The results indicate that the process of reflection is essential for the participants of all groups. However, the participants using the virtual classroom environment scored higher to the reflective items that the control group that tended to be undecided. Moreover, the VR system gave the participants the opportunity to enter the students’ virtual body and understand the different perspectives affecting at a higher level the reflection process than the control group.
Keywords: Reflection skills; Teacher education; Virtual reality